PENENTUAN ISI AWAL MINYAK DITEMPAT DENGAN MENGGUNAKAN METODEMATERIAL BALANCE DAN VOLUMETRIK PADA RESERVOIR ADZ - Dikky Fathurochman Sidiq; Lestari Said (Journal of Mechanical Engineering and Mechatronics, 2018)
Determination of the initial oil content of a reservoir starts from exploration activities. In the initial stage, the determination of the initial oil reserves is determined. This aims to determine whether the project can be profitable for the company or not. Over time the determination of the initial contents of the oil continues to be carried out to improve the accuracy of calculations using the material balance method.In the reservoir "ADZ" the type of reservoir is an undersaturated reservoir. This is because the initial pressure in 1980 was 2762.74 psia, while the bubble point pressure was 1625.8 psia. Until 2015 this reservoir was still above the bubble point pressure with a pressure of 1783.55 psia, this reservoir also had no gas cap in the initial conditions. The drive mechanism that works on this field is the solution for the gas drive.Calculation of the initial content of oil in this final project uses 4 methods, namely volumetric method, material balance method, straight line, and Mbal software. Using the volumetric method, the initial oil reserves obtained at the place amounted to 174063462 STB, while the calculation of the initial oil reserves in place using the material balance method was 176497285 STB. The percentage difference in the initial content of oil between the methods is <5%.